U.G says : everyday thoughts from U.G Krishnamurti - Babani, Arun. (Mumbai : Indus source Books, 2009)
U.G. Krishnamurti's teachings pose a great challenge to the religious traditions all over the world. What UG said was outside the field of teachability. In point of fact, there was no teacher, no taught and there no teaching. There was no symbolism, no metaphysics, no mysticism involved in his words. He meant what he said, literally. This book is a collection of his quotations.
Keywords: Self (Philosophy) -- Quotations, maxims, etc; Krishnamurti, U. G. -- (Uppaluri Gopala) -- Quotations